ANALISIS NILAI SUN PROTECTION FACTOR EKSTRAK ETANOL DAUN KOPASANDA (Chromolaena odorata L.) MENGGUNAKAN SPEKTROFOTOMETRI UV-VIS - Rahmawati, Rahmawati; Muflihunna, A.; Ramadani, Aulia (Fakultas Farmasi UMI, 2024)
Sunlight contains UV rays which have a negative impact on the skin. These bad impacts can be minimized by using UV protective materials, both natural and synthetic. Kopasanda leaves (Chromolaena odorata L) contain high levels of phenolic compounds, flavonoids and tannins. This research aims to determine the UV protection activity of kopasanda leaves (Chromolaena odorata L) using Sun Protection Factor (SPF) calculations. The SPF value was measured using the UV-VIS spectrophotometry method in the wavelength range 290-320 nm. The results of the research showed that kopasanda leaves (Chromolaena odorata L) had protective activity against UV rays at a 1, 3 and 5% re respectively of 31,794, 32,902 and 33,737 (the SPF value categories are ultra).